Forensic evaluation and treatment of juveniles: innovation and best practice - Salekin, Randall T. (American Psychological Association, 2015)
Legal contexts and more -- Juvenile characteristics, political and social climate change, and transfer -- Forensic mental health concepts -- Empirical foundations and limits -- Preparation for the evaluation -- Data collection -- Interpretation -- Report writing and testimony -- Treatment -- Conclusion